CHANGES IN THE MOLECULAR GENETIC PROFILE OF INNATE IMMUNE MOLECULES IN INDIVIDUALS WHO HAVE HAD COVID-19 DISEASE - N. D. Abramova; N. O. Kalyuzhnaya; E. A. Meremianina; E. A. Bogdanova; M. P. Kostinova; O. A. Sviticha (Медицинская иммунология)
AbstractIntroduction. In 2020 COVID-19 was declared to be a pandemic. Since then it was revealed that the severity of the disease pathology may depend not only on the viral strain, but also on the functioning of the immune system. Target. To study characteristics of expression and genetic factors of innate immunity in patients who have had COVID-19. Materials and methods. Material (scrapings from the mucous membranes and venous blood) from 148 patients was studied. Identification of the studied markers was carried out using reverse transcription and RT-PCR methods. Statistical analysis of the results was carried out using the Mann-Whitney test, Fisher's exact test, χ2 test, odds ratio and 95% confidence interval. Results. Our study demonstrated the prognostic role of polymorphic markers and haplotypes in the TLR9 (rs352140 and rs5743836) and TLR4 (rs11536889 and rs4986791) genes in relation to the risk of developing severe SARS-CoV-2 infection. As the result of studying the long-term effects of COVID-19 it was revealed that an imbalance in the expression of receptor and effector molecules at the mucosal level of the immune system remains in patients who have had the disease. There is a decrease in the expression level of both receptor molecules (TLR3, TLR7) and antiviral immune response factors (IL28) in the mucous membranes of the oropharynx with the background of a general increase of these markers in the epithelial cells of the nasopharyngeal mucosa. Conclusion. The expression and genetic factors of innate immunity leading to severe SARS-CoV-2 infection and, consequently, persistent changes in the immune system long after recovery, have been studied, which expands our knowledge of the molecular genetic mechanisms associated with the long-term course of COVID-19. The results obtained during the study can help assess the risks of developing severe infection caused by SARS-CoV-2 and developing complications in hospitalized patients.